A INFLUÊNCIA DA TAXA DE CÂMBIO NAS EXPORTAÇÕES BRASILEIRAS DE CARNE BOVINA IN NATURA - Machado Moraes, Bruna Márcia; Bender Filho, Reisoli; Arruda Coronel, Daniel (Perspectivas Contemporâneas, 2016)
A partir da abertura econômica, nos anos de 1990, o Brasil começou a ter mais visibilidade no mercado internacional de produtos agrícolas. Nesse mesmo período, houve um aumento na demanda mundial por commodities originadas da agricultura e da pecuária, caso da carne bovina, aliada a um aumento de preços, em média, de 60%. Sendo assim, observou-se que a taxa de câmbio desempenha grande influência nas exportações dessas commodities. O objetivo do estudo foi analisar a influência da taxa de câmbio nas exportações líquidas de carne bovina in natura. Para a obtenção de resultados, foi utilizado o modelo do Vetor de Correção de Erros (VEC). Os principais resultados revelam que, no longo prazo, as exportações brasileiras de carne bovina in natura se elevaram mais que proporcionalmente às mudanças cambiais. Já no curto prazo, dado um desequilíbrio na taxa de câmbio, o ajuste se dá de uma forma lenta, em torno de 4,5% em cada período. THE INFLUENCE OF EXCHANGE RATE IN EXPORTS OF BRAZILIAN FRESH BEEF ABSTRACT From the economic opening in the 1990s, Brazil began to have more visibility in the international market of agricultural products. In the same period there was an increase in world demand for commodities originating from agriculture and livestock, combined with a price increase on an average of 60%. Thus, it was observed that the exchange rate played a great influence on the exports of these commodities, as it has changed after the stagnation of the inflation, due to the implementation of the Real Plan. The aim of this paper is to analyze the influence of the exchange rate on net exports of fresh beef. To obtain the results we used the VAR methodology - Vector Autoregressive, and also the VEC- Error Correction Vector and the required tests to complete the model. Thus, the main results obtained show that, in the long run, Brazilian exports of fresh beef rise proportionately more than the exchange rate changes. In the short term, because of an imbalance in the series of the exchange rate, the adjustment takes place in a slow manner, around 4.5% in each period.